2019 International Conference on Speech Technology and Human-Computer Dialogue (SpeD) 2019
DOI: 10.1109/sped.2019.8906577
|View full text |Cite
|
Sign up to set email alerts
|

Sleepiness detection on read speech using simple features

Vincent P. Martin,
Jean-Luc Rouas,
Pierre Thivel
et al.

Abstract: the queuing time and often results in episodic followups with unevenly spaced interviews.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 22 publications
(27 reference statements)
4
21
0
1
Order By: Relevance
“…Moreover, these two modalities were detected with different vocal features, namely prosody features for spontaneous speech and formant-based features for readings. This is in line with the observation made in Martin et al ( 21 ) on the read parts of the SLC: the features have to be adapted to the type of recorded vocal production. In conclusion, both paradigms have benefits and harms: while reading texts keeps the advantage to guarantee a minimum and comparable vocal production along with the recording sessions, spontaneous speech benefits from its closeness with ecological conditions.…”
Section: Guidelinessupporting
confidence: 89%
See 1 more Smart Citation
“…Moreover, these two modalities were detected with different vocal features, namely prosody features for spontaneous speech and formant-based features for readings. This is in line with the observation made in Martin et al ( 21 ) on the read parts of the SLC: the features have to be adapted to the type of recorded vocal production. In conclusion, both paradigms have benefits and harms: while reading texts keeps the advantage to guarantee a minimum and comparable vocal production along with the recording sessions, spontaneous speech benefits from its closeness with ecological conditions.…”
Section: Guidelinessupporting
confidence: 89%
“…The best performances have been obtained by a system based on the ASIMPLS algorithm ( 19 , 20 ) and reach 71.7%. More recently, a work focusing on the longer reading tasks of the SLC has reported an accuracy of 76.4% ( 21 ). Even if this study shows a significant improvement on a subset of the SLC, this performance is still below the necessary 80–85% for medical uses.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, inspired by a previous study [18], we represented in Figure 2c) the performances of the system (a) depending on the threshold to distinguish SL from NSL. This graph represents the specificity of the selected features to the phenomena they aim at measuring.…”
Section: Performances Of the Selected Systemmentioning
confidence: 99%
“…The acoustic features used in this study are presented in detail in [17,18]. They are twofold: on one side, statistics (length and ratio) of voiced and vocalic parts are automatically extracted from audio; on the other side acoustic features are computed on these parts (Harmonics and Formants amplitude and bandwidth, Harmonic to Noise ratio, ...).…”
Section: Acoustic Featuresmentioning
confidence: 99%
“…Even if previous studies have already shown that it is possible to measure subjective sleepiness through voice using extracted vocal features [2,3,4], most of them were based on the Sleepy Large Corpus introduced during the Interspeech 2011 challenge [3] which included only healthy subjects. More recently, the SLEEP corpus has been elaborated for the Interspeech 2019 challenge, paving the way to the use of deep learning in sleepiness detection through voice.…”
Section: Introductionmentioning
confidence: 99%